IMPACT OF OPERATING LEVERAGE AND LEVERAGE ON TAX PROCEEDS ANALYTICAL STUDY IN INDUSTRIAL ENTERPRISES (World Economics and Finance Bulletin, 2023)
The major economic expansion of the modern environment Through the entry of large capital enterprises Large multinational and intercontinental investments and multiple and renewable projects Depending on the evolution of the needs of the markets, this has intensified competition Not only in market shares but also in investments in fixed capital (fixed assets) to produce high quality products taking into account the cost involved Thus, enterprises must seek to invest in fixed assets. This helped maximize profits and increase market shares But this has also contributed to the high risk that enterprises may be exposed to This type of investment is financed through a long-term capital structure As a concern, institutions had to plan properly Proper for this growth of investment and this does not come through operational leverage, Institutions fund their assets through a combination of property and debt rights This is what can be called leverage, so when determining the ratio of the capital structure Money is a debt-to-equity ratio Based on this ratio, projects that have a high money lever should be pursued The high financial leverage ratio means that the rate of return is higher on equity Any increase to cover debts, Different governments provide a large body of services It is financed through taxes linked through various methods of tax accounting The sums are collected from all the real costs and the two economic projects And that's what's called tax revenue. The operational and financial leverage is one of the basic tools Or they can be said to be the ways in which organizations plan their projects and returns And how to invest to achieve these targeted returns that result in tax earnings. The problem with the study is determining the tax outcome of the projects All projects seek to determine the fair value and truth of the taxes they will incur It is linked to them so as to avoid a cut-off and piercing link in case of incorrect value determination Therefore, through operational and financial leverages, net return is planned Which generally results in the value of the tax proceeds Any planned from the beginning of the activity The tax proceeds also reflect the costs charged to the projects, The study's problem can therefore be formulated in the following questions: 1_ What is the impact of operational leverage on tax revenues?
Keywords: formulated; growth; products; markets